Integration of FDOSM and FWZIC under Homogeneous Fermatean Fuzzy Environment: A Prioritization of COVID-19 Patients for Mesenchymal Stem Cell Transfusion - Abdullah Hussein Abdullah Al-Amoodi (Tanjung Malim, 2024)
Integration of FDOSM and FWZIC under Homogeneous Fermatean Fuzzy Environment: A Prioritization of COVID-19 Patients for Mesenchymal Stem Cell Transfusion by Abdullah Hussein Abdullah Al-Amoodi